Justice in the Age of Artificial Intelligence: A Comparative Study of the Legal Framework for Forensic Evidence in Saudi Arabia and Global Practices - Aziz, Dalia Kadry Ahmed Abdel (Journal of Ecohumanism, 2024)
This research paper seeks to explore a potential legal predicament, that arises from integrating artificial intelligence (AI) in extracting and analysing forensic evidence in the Saudi Arabian judicial system. Now, with the rapid growth of AI technologies and its application in criminal investigation, becoming more common, there are many legal and ethical questions that arise. The paper also addresses some important issues, such as the reliability of evidence generated by AI, its admissibility in the courts, and the protection of the defendants’ rights to privacy. The paper then delves into a study of the available legal frameworks in the Kingdom of Saudi Arabia alongside a comparative study of some international systems: the United States, the United Kingdom, the European Union, and the legal framework of China. It shows important lessons learned from these jurisdictions. Furthermore, the findings also suggest several legal and procedural reforms that could be implemented to improve the efficiency and fairness of the Saudi judicial system. These include, inter alia, possible standardization in terms of admissibility of technical evidence, increased transparency in the algorithms used, and judges that have legal and technical training. Thus, the study seeks to suggest pragmatic recommendations to strike the balance between the required efficiency propelled by AI technologies and the governing principles of justice in the Saudi legal environment, which based on Islamic law